EFFECT OF OF LEADERSHIP STYLES ON EMPLOYEES PERFORMANCE AT PT. WAHANA WIRAWAN PALEMBANG - Rumenda, Helmi (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
This study aims to determine the influence of leadership style on employee performance at PT. Wahana Wirawan Palembang. In this study, the force variable is the variable and the performance variable as the dependent variable. Data collection techniques were conducted by interview method, questionnaire, and literature study. Ketin is proposing a round to Likert scale. Test instrument data is done by Test Data Validity with the result of question item valid and Test of Reability with result of all item Question is Trusted. Hypothesis testing with coefficient of determination, Adjusted R-Square value of 0.076, shows that the ratio of leadership style in affecting performance is 7.6%, other variables that cannot be included in this research model. The result of simple regression analysis through t-test is done by knowing the independent variables to the dependent variable of 95% confidence (a = 0,05). The t-test (partially) in the leadership style variable (X) is obtained by tcount (2,423) ˃ttabel (2,002), based on hypothesis test which means performance (Y) by the leadership style.